Singular optics methods for analysis of spatial structure of diffraction field of optical elements - Budnyk, O.P.; Lymarenko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The paper is devoted to developing methods of analytical and experimental investigations of diffraction and interference phenomena used in test systems for optical elements. The theoretical analysis and experimental results illustrate the possibility of describing diffraction phenomena using the objects and methods that were developed in singular optics. It was shown that a system of dislocations in singular component of diffraction field represents its topology. The diffracted field has a system of hidden optical vortices that are smoothly transformed during deformation of an aperture depending on boundary flexion. The proposed experimental proof ground can be useful for the analysis of a wavefront structure. It is also considered the technique for more accurate evaluation of Ronchi test results. The mathematical background of the Ronchi test technique is developed. It describes sufficiently well the wavefront shape, grating plate parameters, image sensor characteristics, parameters of image acquisition and restoration. The fringe pattern distributions and their spatial spectrum are calculated. Both the results of computer simulation of Ronchi fringe pattern and experimental ones obtained using image sensor and the applied image enhancement algorithms are shown.